2009
DOI: 10.2136/sssaj2008.0028
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis‐Gas Chromatography/Mass Spectrometry of Soil Organic Matter Extracted from a Brazilian Mangrove and Spanish Salt Marshes

Abstract: The soil organic matter (SOM) extracted under different vegetation types from a Brazilian mangrove (Pai Matos Island, São Paulo State) and from three Spanish salt marshes (Betanzos Ría and Corrubedo Natural Parks, Galícia, and the Albufera Natural Park, Valencia) was investigated by pyrolysis‐gas chromatography/mass spectrometry (Py‐GC/MS). The chemical variation was larger in SOM from the Spanish marshes than in the SOM of the Brazilian mangroves, possibly because the marshes included sites with both tidal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The methoxyphenols composition recorded in this study is consistent with previous reports from soil organic matter extracted under different vegetation types from a Brazilian mangrove (Pai Matos Island, São Paulo State) using Py-GC/MS techniques (Ferreira et al, 2009). Studies using alkaline CuO oxidation method for the molecular characterization of lignin-derived phenols from sediment of a North Brazilian mangrove ecosystem, indicated that Rhizophora mangle leaves are characterised by high cinnamyl phenol and low content in vanillic units (Dittmar and Lara, 2001).…”
Section: Lignin-derived Phenolssupporting
confidence: 90%
See 1 more Smart Citation
“…The methoxyphenols composition recorded in this study is consistent with previous reports from soil organic matter extracted under different vegetation types from a Brazilian mangrove (Pai Matos Island, São Paulo State) using Py-GC/MS techniques (Ferreira et al, 2009). Studies using alkaline CuO oxidation method for the molecular characterization of lignin-derived phenols from sediment of a North Brazilian mangrove ecosystem, indicated that Rhizophora mangle leaves are characterised by high cinnamyl phenol and low content in vanillic units (Dittmar and Lara, 2001).…”
Section: Lignin-derived Phenolssupporting
confidence: 90%
“…Few studies have used successfully Py-GC-MS technique to relate the biogeochemical signature of mangrove sediments (e.g. Ferreira et al, 2009;Kumar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The wetland sites of Experiment 1 had higher effective moisture than the upland sites (p < 0.05; Figure 2a). The topsoil had marginally lower pH (p = 0.1; Figure 2b) and higher SOC, N, WEOC concentrations and SOC:N ratios in the wetlands than uplands (p < 0.05; Figures 2c, 2d, S3a, and S3b), with the latter reflecting better preservation of plant-derived organic matter (Ferreira et al, 2009) Contrary to our hypothesis, although the absolute concentration of OC CBD was higher in the wetland (23.2 ± 4.1 mg g −1 soil) than upland topsoil (5.3 ± 1.0 mg g −1 soil; p < 0.05; Figure 2h), OC CBD % was comparable (16.1 ± 1.4% and 17.0 ± 1.9%, respectively; p > 0.05; Figure 2i). Nonetheless, this result suggests that in contrast to the common assumption, OC CBD contributes an equally important proportion of SOC in wetlands as in uplands.…”
Section: Oc Cbd Distribution In Contrasting Soilsmentioning
confidence: 98%
“…Whereas of the fatty acids, the C 16 member clearly dominates in litters (up to 1.1%), in soils the C 12 member may reach almost the same abundance. The C 14 , C 16, and C 18 fatty acids can be both plant-derived and microbial, while the C 12 member is usually attributed to microbes (Perobelli Ferreira et al, 2009). Lignin compounds are especially abundant in litters.…”
Section: General Chemistrymentioning
confidence: 99%
“…Pyrolysis-GC/MS provides a large amount of structural information on SOM (De la Rosa et al, 2008;Hatcher et al, 2001;Parsi et al, 2007;Saiz-Jimenez and De Leeuw, 1986), and better identification and comparison of the SOM produced under different environments (Lienweber and Schulten, 1999;Nierop et al, 2001b;Perobelli Ferreira et al, 2009;Saiz-Jimenez et al, 1996). It also provides information on, e.g., selective decomposition and preservation of plant-derived material, admixture of microbial products, and addition of charred material (Buurman and Roscoe, 2011;Buurman et al, 2007b;Kaal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%